2014
DOI: 10.3791/51790
|View full text |Cite
|
Sign up to set email alerts
|

Cerenkov Luminescence Imaging of Interscapular Brown Adipose Tissue

Abstract: Brown adipose tissue (BAT), widely known as a "good fat" plays pivotal roles for thermogenesis in mammals. This special tissue is closely related to metabolism and energy expenditure, and its dysfunction is one important contributor for obesity and diabetes. Contrary to previous belief, recent PET/CT imaging studies indicated the BAT depots are still present in human adults. PET imaging clearly shows that BAT has considerably high uptake of 18 F-FDG under certain conditions. In this video report, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Perkin Elmer micro-CT was applied to analyze brown adipose tissue as described in previous studies ( 40 , 41 ). Briefly, mice were anesthetized with 30 mg/kg pentobarbital sodium and then scanned in the machine to measure BAT volume in the scapula.…”
Section: Methodsmentioning
confidence: 99%
“…Perkin Elmer micro-CT was applied to analyze brown adipose tissue as described in previous studies ( 40 , 41 ). Briefly, mice were anesthetized with 30 mg/kg pentobarbital sodium and then scanned in the machine to measure BAT volume in the scapula.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, other optical approaches, including Cerenkov luminescence imaging, bioluminescence imaging, and photoacoustic imaging, were reported for BAT imaging. Our group has reported that Cerenkov luminescence imaging with 18 F-FDG could be used to monitor BAT activation under different conditions [104,105]. Cheng et al reported that CyHF-8 was capable of noninvasively detecting interscapular BAT with both NIRF and photoacoustic imaging [106].…”
Section: Near-infrared Fluorescence Imaging (Nirfi)mentioning
confidence: 99%
“…Optical techniques are an emerging tool for BAT imaging, especially in rodents. It has been shown that Cerenkov luminescence imaging (CLI) with 18 F-FDG can be used to optically image BAT in small animals ( 25 ). Even though cheaper and faster than PET, CLI again comes with the need for radiotracer injection.…”
Section: Introductionmentioning
confidence: 99%